Genome-Wide Analysis of S. Aureus Strains to Identify Variants Associated with Infection vs. Colonization. (4th October 2017) - Lee, Grace C; Shurko, James; Dallas, Steven; Wang, Yufeng; Olsen, Randall; Lawson, Kenneth; Wilson, James; Frei, Christopher R
Abstract: Background: S . A ureus is an opportunistic pathogen that asymptomatically colonizes its host, but can cause diseases that range in severity from skin and soft-tissue infections (SSTI) to life-threatening cases of pneumonia and endocarditis. The bacterial factors associated with S . A ureus acquisition, infection, and severity are poorly understood. Methods: We sequenced the complete genomes of 144 S . A ureus isolates from patients with either nasal colonization or SSTIs who presented to 10 primary care clinics in South Texas. We then conducted a Genome-Wide Association Study (GWAS) to identify genetic loci that were significantly associated with infection vs. colonization. Significance levels were corrected for multiple tests using the false discovery rate (FDR) procedure. A hierarchical clustering approach was used to estimate the population structures and used as covariates for GWAS stratification. A Random Forest method was used to build a predictive model. The proportions of accurate predictions of phenotypes were reported. Results: GWAS identified 529 variants that were associated with infection vs. colonization. After accounting for population structure, 3 variants (2 nonsynonymous SNPs and 1 insertion) remained statistically significant. One SNP was located in a gene encoding for phosphoglycerate mutase, an enzyme responsible for glycolysis. Another SNP was located in a gene encoding a phage portal protein. A third variant was located in an intergenic region between a transposase and the speG gene within the ACME unit. The Random Forest predictive model demonstrated an accuracy of >88% (misclassification rate of <12%). Conclusion: The candidate loci identified in this study provide a resource for biological studies of S . A ureus pathogenicity. Ultimately, a better understanding of genetic factors associated with disease severity could aid in the management and prevention of S . A ureus infections. Disclosures: All authors: No reported disclosures.